2016
DOI: 10.1016/j.mri.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diffusion-weighted imaging and T2-weighted single shot fast spin-echo: Implications for LI-RADS characterization of hepatocellular carcinoma

Abstract: Purpose To evaluate the performance of diffusion-weighted imaging (DWI) and T2-weighted single shot fast spin-echo (SSFSE) imaging of the liver in the detection of hepatocellular carcinoma (HCC) in reference to the LI-RADS classification system. Methods MR images of 40 patients with 68 LI-RADS grade 3–5 lesions were analyzed. Two readers independently reviewed sequences and characterized lesion signal intensity, followed by consensus evaluation. CE-MRI served as reference standard. Sensitivities were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Rather, it is more important to detect focal hepatic lesions with high sensitivity in high-risk patients. T2WIs have a high sensitivity for detecting focal liver lesions, and DWIs are effective in detecting and characterizing HCC in cirrhotic patients [ 34 , 35 ], especially small HCC (<2 cm) [ 36 ]. In addition, high b-values on DWI offer excellent specificity in distinguishing HCC from benign cirrhotic nodules and pseudo-lesions [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it is more important to detect focal hepatic lesions with high sensitivity in high-risk patients. T2WIs have a high sensitivity for detecting focal liver lesions, and DWIs are effective in detecting and characterizing HCC in cirrhotic patients [ 34 , 35 ], especially small HCC (<2 cm) [ 36 ]. In addition, high b-values on DWI offer excellent specificity in distinguishing HCC from benign cirrhotic nodules and pseudo-lesions [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to ADC measurements, CNR measurements did not differ significantly between the three groups of benign nodules, nodules of intermediate malignancy, and progressed hepatocellular carcinomas. This suggests that the assessment of signal intensity and contrast on high b value images is compounded by mixed effects of diffusion‐weighting and T 2 ‐weighting . Therefore, we think that high b‐value DW images should not be used as surrogates for ADC maps, but ADC maps and high b‐value DW images should be assessed together.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the assessment of signal intensity and contrast on high b value images is compounded by mixed effects of diffusion-weighting and T 2 -weighting. 35 Therefore, we think that high b-value DW images should not be used as surrogates for ADC maps, but ADC maps and high b-value DW images should be assessed together.…”
Section: Discussionmentioning
confidence: 99%
“…19,21 Previous research has demonstrated the clinical potential of mono-exponential DWI or histogram analysis in evaluating the therapeutic response of HCC (for example: TACE or other novel targeted therapies) 22 and diagnostic value in combination with LI-RADS. 23,25 However, hardly ever were IVIM-derived histogram metrics applied for addressing the above issues. In view of the important functional insights provided by IVIM as well as the numerous potential quantitative markers provided by histogram analysis, IVIM-derived histogram metrics held great potential in accurately diagnosing patients with HCC of different grades in the LI-RADS category and evaluating the therapeutic response of TACE and other novel therapies.…”
Section: Diagnostic Performance Analysismentioning
confidence: 99%